EVALUASI PENETAPAN NILAI KRITIS PARAMETER HEMATOLOGI DI INSTALASI LABORATORIUM KLINIK RSUD WATES - PRITA MURANI NUGRAHETI; TEGUH TRIYONO (LP2MTBM MAKARIOZ, 2023)
Timely and accurate reporting critical value of laboratory examination helps support decision making, improves patient safety, and promotes successful therapy. A very extensive or very exclusive list of critical values has the potential to cause problems. This study is aimed to evaluate the determination of critical values, especially hematological parameters, in the Clinical Laboratory Installation of RSUD Wates. This study is a descriptive study of laboratory examination data for hematological parameters at RSUD Wates on January-June 2021. The proportion of critical values is calculated according to the cut off determined by the Clinical Laboratory of RSUD Wates. The cut off of critical values for the Laboratory of RSUP Dr. Sardjito was used as a comparison. The difference in proportion between the two groups was analyzed using the Chi Square test with p<0.05 is statistically significant. The most examination data was leukocyte count (7903 or 25.1%) and the examination with the most critical values is hematocrit (363 or 4.59%). There is a statistically difference in the number of critical values on the parameters of hematocrit, platelet count, leukocyte count and APTT, between the use of the cut off critical value of the clinical laboratory of RSUD Wates compared to the laboratory of RSUP Dr. Sardjito (p<0.01). The different two cut offs has the potential to increase the workload of laboratory staff and more time in reporting critical values. The cut off of critical values at the Clinical Laboratory of RSUD Wates should be reviewed, revised and updated regularly.